A sunset in the Gulf of Paria, Trinidad, B.W.I. - (:unkn) unknown (Muir Marshall and Co.,[Trinidad and Tobago], 2011)
The postcard shows sunset over the Gulf of Paria which is the body of water which lies between Trinidad and the east coast of Venezuela. The Gulf washes the Port of Spain harbour. In the postcard the ships can be seen anchored in the harbour.
Colour: Black and White, Sepia; Style: Landscape; Other: Bordered, Divided
Keywords: Trinidad and Tobago; Postcards; Sun--Rising and setting; Paria, Gulf of (Venezuela and Trinidad and Tobago)